2021
DOI: 10.1016/j.ccell.2020.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Cathepsin C promotes breast cancer lung metastasis by modulating neutrophil infiltration and neutrophil extracellular trap formation

Abstract: Highlights d Tumor-secreted CTSC promotes breast-to-lung metastasis by regulating neutrophils d CTSC activates membrane-bound PR3 of neutrophils to upregulate IL-1b secretion d CTSC enhances neutrophil recruitment into metastatic niches and induces NETosis d Targeting CTSC with AZD7986 effectively inhibits lung metastasis in mice

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
300
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 372 publications
(306 citation statements)
references
References 77 publications
(102 reference statements)
5
300
0
1
Order By: Relevance
“…The formation of NETs may be partly due to the hypoxic environment in which growing solid tumors are generated concomitant with the higher expression of HIF-1α [ 20 , 21 ]. Moreover, secreted cytokines [ 18 , 48 , 58 , 64 , 67 ], proteases [ 68 ] and even exosomes [ 57 ] may also contribute to NET formation ( Figure 1 ). Depletion of IL-8, G-CSF, GROα or GROβ derived from ovarian cancer cells can incompletely reduce NET formation and neutrophil chemotaxis, suggesting that these cytokines cooperate with each other to optimally stimulate neutrophil mobilization and NET formation [ 65 ].…”
Section: Net Formationmentioning
confidence: 99%
See 4 more Smart Citations
“…The formation of NETs may be partly due to the hypoxic environment in which growing solid tumors are generated concomitant with the higher expression of HIF-1α [ 20 , 21 ]. Moreover, secreted cytokines [ 18 , 48 , 58 , 64 , 67 ], proteases [ 68 ] and even exosomes [ 57 ] may also contribute to NET formation ( Figure 1 ). Depletion of IL-8, G-CSF, GROα or GROβ derived from ovarian cancer cells can incompletely reduce NET formation and neutrophil chemotaxis, suggesting that these cytokines cooperate with each other to optimally stimulate neutrophil mobilization and NET formation [ 65 ].…”
Section: Net Formationmentioning
confidence: 99%
“…Xiao et al found that the tumor-secreted protease cathepsin C (CTSC) enzymatically activates neutrophil membrane-bound proteinase 3 (PR3) to upregulate IL-6 and CCL3 for neutrophil recruitment. In addition, the CTSC–PR3–IL-1β axis induces the formation of NETs which support the metastasis of cancer cells in the lungs [ 68 ]. Furthermore, tumor-derived exosomes have been closely linked to NET formation.…”
Section: Net Formationmentioning
confidence: 99%
See 3 more Smart Citations